Urban renovation of portuguese historical centres - Castanheira, Guilherme (2012)
Cities are ecosystems that consume a lot of energy and substance, as well as generate much waste and pollution. Concerns about waste and misuse of natural resources have led people and governments to think better about urban growth. Nowadays half of world population lives in cities, and it is expected a considerable increase over the next years in developing countries. Already in some European Union countries, which currently go through times of crisis, it is misunderstood the necessity of cities expansion. Portugal is one of these developed countries, with many historical cities and non-necessity of expansion, but a need for changes, which accompany the world development and their sustainable premises. The way cities in Portugal should evolve, goes through the sustainable renovation, whether urban or buildings. In the scope of sustainable rehabilitation as well as in the conception of sustainable projects, it is important to consider the, inevitably connected, environmental, social, economic and cultural aspects. The main objective of this paper is to discuss urban renovation, which should be resilient, should know how to add value to the environment where people live in, taking advantage of cities elements, through the technological evolution and rational use of natural resources, sustainable materials and techniques.